2017
DOI: 10.1007/s13632-017-0402-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition and Characterization of Ni–W–Cr2O3 Nanocomposite Coating

Abstract: In this paper, compact Ni-W and Ni-W-Cr 2 O 3 nanocomposite coatings were deposited on mild steel substrates by DC electrodeposition method. The surface morphology, elemental composition, and structure of the obtained coatings were investigated by scanning electron microscopy, energy dispersive spectrometer, and x-ray diffraction. The corrosion resistance was evaluated by potentiodynamic polarization (Tafel) and electrochemical impedance spectroscopy. It is shown that incorporation of Cr 2 O 3 nanoparticles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
3
2
1
Order By: Relevance
“…At 20 g•L −1 , the coatings display a more amorphous tendency characterized by cavities. Similar observations were reported by Zhang et al [21].…”
Section: Effects Of Cr2o3 Nanoparticles On Ni-w/cr2o3 Nanocompositessupporting
confidence: 92%
See 4 more Smart Citations
“…At 20 g•L −1 , the coatings display a more amorphous tendency characterized by cavities. Similar observations were reported by Zhang et al [21].…”
Section: Effects Of Cr2o3 Nanoparticles On Ni-w/cr2o3 Nanocompositessupporting
confidence: 92%
“…At 20 g•L −1 , the coatings display a more amorphous tendency characterized by cavities. Similar observations were reported by Zhang et al [21]. From the current efficiency analysis, it was found that Ni-W coatings with 11.0 wt.% W content had a current efficiency of 42.05% compared to 32.82% for Ni-W/Cr2O3 electrodeposited with 10 g•L −1 Cr2O3 nanoparticles.…”
Section: Corrosion Resistancesupporting
confidence: 89%
See 3 more Smart Citations